Integrasi Game-Based Learning dan Scratch dalam Pembelajaran IPAS untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Izzuddin Kafi; A.F. Suryaning Ati MZ; Mochammad Miftahul Huda (Mataram University, 2026)
Amid the shift toward digital and interactive learning encouraged by Indonesia’s Kurikulum Merdeka, the integrated Science and Social Studies (IPAS) subject is still largely taught through lecture-based and memorization methods, leaving abstract material such as light energy difficult for elementary students to grasp. While prior studies have examined Game-Based Learning and Scratch-based media separately, few have investigated their integration within IPAS instruction at the elementary level, a gap this study addresses. This study aimed to describe teacher activity, student activity, and the improvement of IPAS learning outcomes through the application of the Game-Based Learning model assisted by Scratch media in Grade V of MI Muhammadiyah 03 Pucakwangi. This study employed a Classroom Action Research (CAR) approach using the Kemmis & McTaggart model conducted in two cycles, with 23 Grade V students as subjects. Data were collected through tests (pretest and posttest), observation, and documentation, then analyzed descriptively and quantitatively. The results showed that classical learning completeness increased from 56.52% in Cycle I to 86.96% in Cycle II, teacher activity increased from 68.75% to 95.31%, and student activity increased from 62.50% to 85.94%. These findings imply that integrating Game-Based Learning with Scratch media offers a practical, technology-based instructional alternative that strengthens conceptual understanding and active participation, and can serve as a reference model for elementary teachers designing more engaging science instruction. However, the study was limited to a single topic (Light Energy) and depended on access to computers or laptops with a stable internet connection. Therefore, further research is recommended to evaluate the applicability of this model across a broader range of instructional materials, subject areas, and educational levels, as well as to explore the use of the offline version of Scratch in schools with limited access to device and internet connectivity.